TANGGUNG JAWAB PENJUAL DALAM TRANSAKSI JUAL BELI ONLINE DITINJAU DARI HUKUM PERDATA (CONTOH KASUS: PUTUSAN NOMOR 183/PDT.G/2018/PN MDN) - Kelly Kelly; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
Buying and selling between buyers and the Elipa Store throught the WhatsApp application can be considered valid as long as it fulfills the legal requirements of an agreement as regulated in article 1320 of the civil code. In a sale and purchase agreement, the parties must carry out their respective achievements that they have promised in the sale and purchase. If the seller does not carry out his achievements, how is the seller’s responsibility in online buying and selling transactions in terms of civil law (case example: decision number 183/Pdt.G/2018/PN Mdn)? in this paper, the author uses a normative approach by examining various existing library materials and also the results of interviews. In this example, the seller does not carry out his achievements in the form of submitting and delivering what has been ordered and paid for by the buyer, so the seller is considered to have defaulted. Not only that, in this study the author also found that in addition to default, the seller had also violated article 63 paragraph (1) of PP PMSE. With the loss arising from the seller’s actions, the seller must be responsible for his actions to bear all sanctions in accordance with the violations stipulated in the civil code and PP PMSE.